PENGOLAHAN WADI IKAN PATIN (Pangasius hypophthalmus) PROSES CEPAT DAN TIDAK ASIN - Restu Yuda Bakrie (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study aims to determine processing of wadi patin fish (Pangasiu hypophthalmus) quick process and not salty, It is a fermented product from fish, in the form of a wet material through a salting process, the addition of spices then followed by fermentation for several days until it produces an aroma and taste. This traditional food is the result of fermentation assisted by synergistic microorganisms, namely lactic acid bacteria. The results of the study by washing fish after the salting process were able to accelerate fermentation from 7 days to 3 days. The best treatment is to wash the fish meat twice after the salting process. the specifications of the resulting wadi are as follows: protein content = 18.64%; salt content = 0.79%; Water content = 58.65%; Fat content = 3.29%; total microbes (LAB) 6.5x104; organoleptic value (taste) = 7.55.